Incidents and disaster avoidance: the role of communication management and the organizational communication climate in high-risk environments - Nordin S.M.; Rizal A.R.A.; Rashid R.A.; Che Omar R.; Priyadi U. (MDPI, 2023)
accident; communication; complexity; environmental management; environmental risk; gas industry; innovation; oil industry; oil spill; safety; working conditions